2006
DOI: 10.1099/jmm.0.46027-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a routine laboratory direct detection system of staphylococcal enterotoxin genes

Abstract: A novel direct detection system has been developed for eight staphylococcal enterotoxin (SE)-encoding genes (sea, seb, sec, sed, see, seg, seh and sei) in milk. Specific detection by real-time PCR was successful for all SE-encoding genes in the reference strains. Furthermore, a novel DNA-preparation method with good reproducibility [coefficients of variation 0?31, 0?99 and 1?21 % at 10 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…The past reports from Germany suggest that Ct for fem B gene was between 21.8-33.7 and 22.5-33.5 for Se a gene [29]. Nakayama et al [9] detected eight Se-encoding genes in the S. aureus of milk sample, and the Ct value detection limit of Se encoding gene was between 39.44 and 37.92.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The past reports from Germany suggest that Ct for fem B gene was between 21.8-33.7 and 22.5-33.5 for Se a gene [29]. Nakayama et al [9] detected eight Se-encoding genes in the S. aureus of milk sample, and the Ct value detection limit of Se encoding gene was between 39.44 and 37.92.…”
Section: Resultsmentioning
confidence: 99%
“…However, RT-PCR method of direct detection of Se from the sample is more sensitive and rapid than that of RPLA method. Furthermore, the RT-PCR method was also proved to be a successfully applicable technique for direct detection of Se from the clinical samples that contain high levels of PCR inhibitors [9]. Rajkovic also compared iqPCR with inhouse ELISA technique for detecting Se b toxin genes in both pure culture and contaminated food sample and found that iqPCR was approximately 1,000 times more sensitive than the in-house ELISA method [25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Milchpulver entwickelt. Nakayama et al (2006) konnten sea -sei in künstlich kontaminierter Milch mit Nachweisgrenzen von 10 2 -10 4 KbE/ml nachweisen. Ikeda et al (2005b) untersuchten in Zusammenhang mit einem Ausbruch durch SEA-bildende S. aureus Milchpulver quantitativ auf sea, um damit indirekt auf die Belastung mit S. aureus zu schließen.…”
Section: Polymerasekettenreaktionunclassified